Silicon optical modulator simulation - Lim, Soon Thor; Sun, Min Jie; Png, Ching Eng (Frontiers in Physics, 2015)
We developed a way of predicting and analyzing high speed optical modulator. Our research adopted a bottom-up approach to consider high-speed optical links using an eye diagram. Our method leverages on modular “mapping” of electrical characteristics to optical characteristics, while attaining the required accuracy necessary for device footprint approaching sub-micron scales where electrical data distribution varies drastically. We calculate for the bias dependent phase shift (2pi/mm) and loss (dB/mm) for the optical modulator based on the real and imaginary part of complex effective indices. Subsequently, combine effectively both the electrical and optical profiles to construct the optical eye diagram which is the essential gist of signal integrity of such devices.